Pengaruh Media Sosial, Hubungan Masyarakat, dan Persepsi Kualitas terhadap Citra Institusi melalui Kepuasan Pelanggan sebagai Variabel Intervening pada Badan Pelindungan Pekerja Migran Indonesia - Nugroho, Tulus Setyo; Sutisna, Sutisna; Komarudin, Mamay (Universitas Islam Kadiri, 2025)
This study aims to analyze the influence of social media, public relations, and service quality on the institutional image of BP2MI (Indonesian Migrant Worker Protection Agency) through user satisfaction. Institutional image refers to public perception of an organization’s performance, which is crucial in building public trust and enhancing BP2MI's ability to carry out its duties and functions. In recent years, the number of complaints from migrant workers has increased, indicating persistent issues in protection and services provided by BP2MI. Therefore, this research employs a quantitative approach with a survey method targeting BP2MI service users to examine the extent to which the independent variables (social media, public relations, and service quality) affect the dependent variable (institutional image) mediated by satisfaction. The findings reveal that social media, public relations, and service quality significantly influence user satisfaction, which in turn shapes a positive institutional image. This study recommends enhancing public communication strategies and developing more adaptive digital services to increase user satisfaction and strengthen the agency’s image.